Semantics for Attribute-Value Theories - Osswald, Rainer (Proceedings of the Amsterdam Colloquium, 1999)
Attribute-value (AV) descriptions are reconstructed from natural language by regimentation and formalization within first-order predicate logic. The introduction of appropriate predicate operators then leads to AV expressions of the usual Kasper-Rounds type. We present a slight extension which permits relations between attribute values. A straightforward modification of standard AV logic turns out to be sound and complete with respect to first-order derivability granted that attributes are functional. Demonstrating this is part of our second concern which is to apply geometric logic and locale theory to AV theo-ries like HPSG. Viewing AV theories as propositional geometric theories provides a crisp characterization of the denotation of an AV theory as the point space of its classifying locale.